All‐Solid‐State Mechanochemical Synthesis and Post‐Synthetic Transformation of Inorganic Perovskite‐type Halides. Issue 8 (16th January 2018) - Pal, Provas; Saha, Sujoy; Banik, Ananya; Sarkar, Arka; Biswas, Kanishka
Abstract: All‐inorganic and hybrid perovskite type halides are generally synthesized by solution‐based methods, with the help of long chain organic capping ligands, complex organometallic precursors, and high boiling organic solvents. Herein, a room temperature, solvent‐free, general, and scalable all‐solid‐state mechanochemical synthesis is demonstrated for different inorganic perovskite type halides, with versatile structural connectivity in three (3D), two (2D), and zero (0D) dimensions. 3D CsPbBr3, 2D CsPb2 Br5, 0D Cs4 PbBr6, 3D CsPbCl3, 2D CsPb2 Cl5, 0D Cs4 PbCl6, 3D CsPbI3, and 3D RbPbI3 have all been synthesized by this method. The all‐solid‐state synthesis is materialized through an inorganic retrosynthetic approach, which directs the decision on the solid‐state precursors (e.g., CsX and PbX2 (X=Cl/Br/I) with desired stoichiometric ratios. Moreover, post‐synthetic structural transformations from 3D to 2D and 0D perovskite halides were performed by the same mechanochemical synthetic approach at room temperature. Abstract : Daily grind : Inorganic perovskite‐type halides with different structural connectivity were synthesized by a simple, room temperature, scalable all‐solid‐state mechanochemical grinding method. Post synthetic structural transformations from 3D to 2D and 0D halides and vice‐versa have been achieved by the same all‐solid‐state synthesis.